Treatment Options in Isolated Atherosclerotic Popliteal Artery Disease - Stephanie Rassam; Raphaël Coscas (Journal of Cardiovascular Development and Disease)
Isolated popliteal artery (PA) lesions account for around 1% of lower limb revascularisations. Whatever treatment modality is chosen, the effects on the artery during knee flexion must be considered. The decision between a less invasive endovascular treatment (EVT) and traditional open interventions remains complex due to anatomical, biomechanical, and pathophysiological considerations and the varying aetiology of PA lesions. Available data remain limited, making it more challenging to decide on the most effective and durable treatment approach. Nowadays, when EVT is planned, several non-stenting techniques are available, making a “leave-nothing-behind strategy” possible after adequate vessel preparation. If stent implantation is required, self-expanding vasculomimetic stents are preferred due to their ability to provide flexibility and resist compression during motion. This narrative review discusses the available treatment options, challenges, and specific considerations for isolated PA disease, highlighting the need for large-scale, high-quality studies to provide more robust evidence on the optimal treatment approach.